Assessment of drought using Standardized Precipitation Index (SPI) for Yusmarg area of Jammu and Kashmir - KHAN, SAMREEN; KUMAR, ROHITASHW; PANDIT, BASHIR AHMAD; AHMAD, LATIEF; ARAIN, NIMRA (Journal of Soil and Water Conservation, 2025)
Drought is a natural disaster which is characterized by intense and persistent shortage of precipitation. Drought monitoring plays important role for the freshwater planning and management as well as for prediction of the onset and severity of droughts. Over the years several indices have been proposed to monitor and quantify information regarding droughts. The most widely accepted index is Standardized Precipitation Index (SPI) which is based on probability concept. The present study deals with the potential of using precipitation-based SPI to analyse the temporal pattern of drought and its severity in the Budgam district of Jammu and Kashmir during 2003-2022 (20 years). The study was used “DrinC” software. Monthly precipitation data from 2003 to 2022 for Yusmarg region were used to compute SPI values. The computation of SPI series was done for short, intermediate as well as for long time scales. The study revealed four moderate drought in the Yusmarg region occurred in 2007, 2009, 2012, and 2016. Also, no severe drought occurred during the period 2003-2022. The intensity with highest SPI value for moderate drought was the year 2007 with (-) 1.37.